Pengaruh Bahan Perbanyakan Tanaman dan Jenis Pupuk Organik Terhadap Pertumbuhan Tanaman Binahong (Anredera cordifolia (Ten.) Steenis) - Dan Baskoro; Bambang S. Purwoko (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2011)
This research was aimed at studying the effect of plant propagation material and organic fertilizer on Anredera cordifolia [Ten.] Steenis growth. The experiment was conducted at the Sawah Baru Experimental Field, IPB from March to June 2010. This study was laid out in a factorial randomized block design consisting of two factors. The first factor was the plant material i.e. two types of planting materials, root rhizome and stem cuttings with leaves. The second factor was the type of organic fertilizer i.e. without fertilizer as the control, combination of soil and organic fertilizer 1:1 (v/v), i.e. compost, cow manure, and chicken manure. The result showed that stem cutting gave higher plant height, leaf number and width and number of branches. Treatment of planting medium significantly affected plant height, number and width of leaf, fresh and dry weight of roots, stems and total weight of fresh leaf. Cow manure gave the best effect. Interaction of plant propagation material and organic fertilizer only significantly affected plant height at 2 Week After Planting (WAP) and root dry weight. Stem cuttings is a better plant propagation material on all types of organic fertilizer than rhizome.Key words:organic fertilizer type, propagation materials, Anredera cordifolia